2015
DOI: 10.1118/1.4934375
|View full text |Cite
|
Sign up to set email alerts
|

Image‐derived and arterial blood sampled input functions for quantitative PET imaging of the angiotensin II subtype 1 receptor in the kidney

Abstract: The bias of radioligand concentration in the aorta from the OS-EM image reconstruction is significantly affected by radioligand uptake in the adjacent kidney and cannot be neglected for quantitative evaluation. With careful calibrations and corrections, the ID-IF derived from quantitative dynamic PET images can be used as the input function of the compartmental model to quantify the renal kinetics of 11C-KR31173 in experimental animals and the authors intend to evaluate this method in future human studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…Therefore a Logan graphical analysis is assumed to be less dependent on the accurate determination of the rapidly changing peak of the input function which could be poorly estimated 23 . This is confirmed by several previous studies 25 , 38 , 39 . However, since metabolization of [ 18 F]JNJ-739 is rather fast (only 30% ± 5% of parent tracer at 20 min post-injection), the contribution of later time points of the metabolite-corrected arterial plasma input function is limited such that cumulated activity concentrations at later time points, which are used for the Logan graphical analysis estimation, are more dependent on the accurate estimation of peak activity concentrations, shortly after tracer injection.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Therefore a Logan graphical analysis is assumed to be less dependent on the accurate determination of the rapidly changing peak of the input function which could be poorly estimated 23 . This is confirmed by several previous studies 25 , 38 , 39 . However, since metabolization of [ 18 F]JNJ-739 is rather fast (only 30% ± 5% of parent tracer at 20 min post-injection), the contribution of later time points of the metabolite-corrected arterial plasma input function is limited such that cumulated activity concentrations at later time points, which are used for the Logan graphical analysis estimation, are more dependent on the accurate estimation of peak activity concentrations, shortly after tracer injection.…”
Section: Discussionsupporting
confidence: 92%
“…Partial volume effects (PVE) between PET activity concentration in the carotid arteries ( ) and corresponding background were modeled as: where and represented the whole blood activity concentration and the PET activity concentration in the background VOI, respectively, while w was the partial volume weighting factor which models the spill-in and spill-over effects ( ) between background and carotid arterial activity 25 27 .…”
Section: Methodsmentioning
confidence: 99%
“…The variance of the estimation can be high for voxel‐wise analysis. Another disadvantage of such method is the requirement for accurate plasma input functions, which either requires invasive blood sampling or longer acquisitions from the beginning of injection to generate image‐derived input function 14 . As a result, graphical methods such as Patlak analysis have been widely adopted due to its simplicity and robustness 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Another disadvantage of such method is the requirement for accurate plasma input functions, which either requires invasive blood sampling or longer acquisitions from the beginning of injection to generate image-derived input function. 14 As a result, graphical methods such as Patlak analysis have been widely adopted due to its simplicity and robustness. 15 Studies have shown that Patlak slope is a more accurate index of glucose metabolic rate than SUV because of the unmetabolized FDG measured by SUV and the inability of SUV to account for the available dose.…”
mentioning
confidence: 99%
“…In some studies, the requirement of invasive arterial blood sampling for the input function makes the scan protocol impractical. Even with the use of image-derived input functions (18,19) or population-based input functions (20,21), a minimal scan time of 30 minutes is often required to reveal dynamic information using Patlak analysis. Compared with state-of-art whole-body SUV scans which take around 20 minutes and some in less than 10 minutes, the increased scan time and more complex protocol have shown to be one of the major practical factors that hinder the clinical use of dynamic analysis with whole-body imaging.…”
Section: Introductionmentioning
confidence: 99%